Keragaman Morfologi dan Komponen Hasil Kubis Bunga (Brassica oleracea var. botrytis L.) di Dataran Tinggi dan Dataran Rendah - Sobir; Haryanti, Dyra; Efendi, Darda (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Increasingly limited land in the high elevation and increasing of global temperature needed breeding of cauliflower plants originating from temperate regions to be adaptively planted in low elevation. This study aimed to identify the morphological variability and yield component of cauliflower planted in the high elevation and low elevation. The experiment was conducted in Pasir Sarongge (1,117 m asl) and Tajur II (340 m asl) from June to December 2016. This experiment was conducted with a randomized complete block design single-factor (12 genotypes of cauliflower) with three replications. The results showed that BOB 021 genotype was not flowering in Tajur. Qualitative characteristics that are stable in two locations include leaf attitude, leaf color, curd color, leaf lobing, and curd covering by inner leaves. Vegetative characters and yields in low elevation were higher than high elevation, time of flowering and harvesting in high elevation was earlier than in low elevation. Based on the correlation analysis, an increase in the yield characters can be seen from the increase in vegetative character and increase in longevity time of flowering and harvesting. Keywords: correlation, flowering, qualitative, quantitative